Clonal evolution in myelodysplastic syndromes - Pedro da Silva-Coelho; Leonie I. Kroeze; Kenichi Yoshida; Theresia N. Koorenhof‐Scheele; Ruth Knops; Louis T. van de Locht; Aniek O. de Graaf; Marion Massop; Sarah Sandmann; Martin Dugas; Marian Stevens‐Kroef; Jaroslav Čermák; et al. (2017)
Abstract Cancer development is a dynamic process during which the successive accumulation of mutations results in cells with increasingly malignant characteristics. Here, we show the clonal evolution pattern in myelodysplastic syndrome (MDS) patients receiving supportive care, with or without lenalidomide (follow-up 2.5–11 years). Whole-exome and targeted deep sequencing at multiple time points during the disease course reveals that both linear and branched evolutionary patterns occur with and without disease-modifying treatment. The application of disease-modifying therapy may create an evolutionary bottleneck after which more complex MDS, but also unrelated clones of haematopoietic cells, may emerge. In addition, subclones that acquired an additional mutation associated with treatment resistance ( TP53 ) or disease progression ( NRAS , KRAS ) may be detected months before clinical changes become apparent. Monitoring the genetic landscape during the disease may help to guide treatment decisions.